INTERNAL CONTROL ROLE IN RELATIONSHIP BETWEEN EMPLOYEE AND PUBLIC SECTOR ORGANIZATIONS - Andriono, Rian; T, Sutrisno; Nurkholis, Nurkholis (Jurnal Aplikasi Manajemen, 2018)
This study aims to obtain empirical evidence of the impact of employee's Public Service Motivation (PSM) and Organizational Commitment on the Organizational Performance through Internal Control System (ICS) as an intervening variable. The study was conducted on all State Civil Employees at the State Treasury Services Office in Bali Province through a survey on 98 respondents and was analyzed with SEM-PLS. The results show that Organizational Performance improvement in order to achieve performance contract's designated targets done by increasing employee's motivation and commitment. PSM and Organizational Commitment play an important role in goals achievement, and without both variables, the performance management will not lead to higher public services quality. Public sector organizations can make ICS as a tool to controls over employee's motivation and commitment. The integrated ICS within the organizational unit structure is not only able to controls the overall business process but also on the employee's daily work life.